Volatilization Characteristics of High-lead Slag and its Influence on Measurement of Physicochemical Properties at High Temperature - Guohua Wang; Yaru Cui; Zhe Yang; Ziliang Guo; Xiaoming Li; Junxue Zhao; Wendan Tang (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
Volatilization causes deviations in the measurement of physicochemical properties for volatiles-containing slag at high temperature. Hence, investigating the degree of volatility and identifying the volatilization mechanism and deviation rules are crucial to improving the accuracy of the measured properties. Here, PbO-FeOx-CaO-SiO2-ZnO slag was selected as a research subject. The volatile characteristics and non-isothermal intrinsic kinetic models of high-temperature volatilization for lead slags were established by thermogravimetric analysis (TGA), and the volatilization mechanism and deviation in the measured properties were determined by analyzing the phase and chemical composition of the residues. In addition experimental measurements of the melting temperature/viscosity were compared with theoretically calculated results. The volatilization of PbO decreases the lead-containing phase but increases the amount of precipitated spinel phase, which leads to the deviation in the measured physicochemical properties of the studied slags. The volatilization kinetics for PbO in the slags followed three-dimensional diffusion. The restrictive step of the volatile reaction is the diffusion of PbO gas, and its mechanism function is g(α)=1-(1-α)^(1/3). During the slag property measurements, a high heating rate and protective gas can be used to reduce volatilization and avoid consequent deviations in the properties measured at high temperatures